Hubungan antara Produk Domestik Bruto, Ekspor, dan Impor dengan Utang Luar Negeri di Indonesia: Studi Kasus Periode 2010–2022 - Isra, Isra; Muzakir, Muzakir (Medan Resource Center, 2024)
This study examines the relationship between Gross Domestic Product, exports, imports, and Indonesia’s external debt over the period 2010–2022, against the backdrop of increasing reliance on foreign borrowing to support economic development. The research addresses the question of how key macroeconomic variables influence the dynamics of external debt in Indonesia. Employing a quantitative approach, this study utilizes multiple linear regression analysis based on secondary time-series data to assess both the direction and significance of these relationships. The empirical results reveal that Gross Domestic Product has a positive and statistically significant effect on external debt, indicating that economic growth is accompanied by higher foreign borrowing. Exports are found to have a negative and significant effect, suggesting that stronger export performance contributes to reducing external debt pressures. In contrast, imports do not exhibit a statistically significant relationship with external debt. The study argues that export expansion plays a critical role in strengthening debt sustainability, while economic growth alone does not automatically reduce reliance on external financing. These findings provide important implications for macroeconomic policy, particularly in balancing growth strategies with external debt management.